BOOK REVIEW: PRESENTING IN ENGLISH: A PRACTICAL GUIDE - Athapaththu, Pasan (LLT Journal: A Journal on Language and Language Teaching, 2025)
Authored cautiously, keeping in mind the individuals who find it challenging to deliver presentations in English, Presenting in English: A Practical Guide by Dick Smakman is a potential candidate to occupy space on the bookshelf of any student genuinely seeking straightforward advice for their presentations. As presentations are a powerful persuasive tool (Duarte, 2010) and the most transferable of all other skills (Van Emden Becker, 2016), a majority of modules in educational programmes have allocated space for a component on presentation skills (Grieve et al., 2021).